Effects of low-volume court-based sprint interval training on aerobic capacity and sport-specific endurance performance in competitive tennis players - Yang, Wenpu; Yin, Langlang; Poon, Eric Tsz-Chun; Kit Ho, Indy Man; Liu, Haochong; Qi, Bing; Li, Qian; Li, Yanchun (Biology of Sport, 2025)
Sprint interval training (SIT) is a potent exercise strategy to enhance athletes’ aerobic capacity in a time-efficient manner. The purpose of this study was to examine the effect of a low volume court-based SIT program on aerobiccapacity and sport-specific endurance performance forcompetitive tennis players. Sixteen competitive collegiate tennis players were randomly assigned to the SIT (court-based repeated-sprint training) and traditional endurance training (ET; 45-min continuous treadmill running) groups for a 6-week intervention (3 sessions/week). The maximal oxygen uptake (V̇ O 2max ), minute ventilation at peak exercise (VEmax), ventilatory anaerobicthreshold in percentage of V̇ O 2max (VT/VO 2 ), and elimination rate of blood lactate (BLA er ) were assessed, whereas the Yo-Yo Intermittent Recovery Test Level 2 (YoYo-IR2) and the tennis-specific HIT&TURN test were conducted at baseline and after the intervention. Both SIT and ET showed significant improvements in V̇ O 2max ( p < 0.01) with moderate effect sizes (ES = 0.64 and 0.98, respectively), as well as in VE max ( p < 0.01) with small effect sizes (ES = 0.23 and 0.21, respectively), and VT/VO 2 ( p < 0.01) with large effect sizes (ES = 2.37 and 3.85, respectively). The BLA er improved significantly in SIT (ES = 1.03; p < 0.05) whereas no significant changes occurred in ET. The magnitude-based decision showed a clear and superior improvement in both YoYo-IR2 (ES = 0.69) and HIT&TURN (ES = 1.72) tests in SIT than ET. Compared with traditional ET, court based SIT can be a time-efficient strategy to improve aerobic capacity and tennis-specific endurance without requiring specialized equipment for competitive tennis players.